Considerações sobre desmame em bovinos de corte - (:unkn) unknown (Universidade Federal do Pampa, 2011)
Brazil has a cattle population of 174 million head, with a number of slaughtering 40 million cattle, is the second largest producer of beef and the largest exporter of beef in the world, with per capita consumption in 2009 38.8 kg / person / year. These data demonstrate the importance of Brazilian beef cattle breeding and the great possibility of expanding exports and marketing of beef. On the other hand is identified the necessity to adapt more technical systems for the improvement of production indices. The improvement rates of the Brazilian cattle industry is enjoying the increased of pregnancy rates, which represents the index of greater impact on the overall productivity of the breeding herd, and that can be achieved with the adoption of specific management techniques such as early weaning of calves, especially in properties that present pregnancy rates less than 65%, and is a practice that can raise the birth rate with relative ease, cost and compatible with good acceptance by the producer. In addition to improving pregnancy rates, it is important to improve cow body condition and can therefore be combined with a tool for reproduction and the possible disposal of arrays, generating greater profitability on the farm. Looking at the different European and zebu blood, we can evaluate the advantages and disadvantages of weaning in relation to the races.
Keywords: Desmame precoce; Eficiência reprodutiva; Bovinos de corte; Early weaning; Reproductive efficiency; Beef cattle; Zootechny; Zootecnia; CNPQ::CIENCIAS AGRARIAS